Implementasi Metode Bernyanyi dalam Meningkatkan Kecerdasan Musikal Anak Usia Dini di RA Fatipa - Fauziah Nasution; Amanah Putri Fadillah; Andina Zahra; Fannia Sri Juwita; Nia Alfiyalawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to describe the implementation of singing methods in enhancing the musical intelligence of early childhood at RA Fatipa and to analyze its impact on the holistic development of children. Using a descriptive qualitative method with participatory observation techniques, in-depth interviews, and document studies, this research finds that the singing method at RA Fatipa is implemented integratively through various techniques, such as singing together, singing with movements, and using songs as learning media. The research results show a positive impact of the singing method on children's musical intelligence, cognitive development, language, socio-emotional, and motor skills. However, the study also identifies several challenges, namely limitations in facilities and infrastructure, the need for teacher training, the importance of parental support, as well as the need for a more systematic integration of the curriculum and strengthening of the evaluation and documentation system. This study recommends improving facilities and infrastructure, continuous training for teachers, active parental involvement, better curriculum integration, and the development of a structured evaluation and documentation system to optimize the implementation of singing methods and their impact on children's development.